Self-healing and recyclable polyimide hybrid film with linear and crosslinked bridging structure - Wan, Baoquan; Liu, Huizhu; Wang, Jiangqiong; Xing, Yunqi; Gao, Jiefeng; Jung, Yong Chae; Zha, Jun-Wei (Pergamon Press Ltd., 2025)
Polyimide (PI) will be gradually damaged under long-term stress, resulting in equipment failure. The current research still faces the difficulty of the performance degradation of regenerative PI hybrid dielectrics. The rigid molecular structure hinders the self-healable or recyclable capability and performance recovery of traditional PI after damage. Herein, a self-healing crosslinked polyimide (SCPI) has been successfully developed. The linear and crosslinked bridging structures formed by trifunctional aldehydes and bifunctional aldehydes in SCPI films balance the contradiction between reversible structure and performance recovery in the system. The SCPI films show excellent healing ability and polymer-solution recycling properties for many forms of damage. The crosslinked structure enabled the films to maintain their extreme tensile strength (σt = 106 MPa) and electrical breakdown strength (Eb = 418 MV/m). Furthermore, carbon fiber reinforced composites (CFRCs) with strong load-bearing capacity are fabricated by compositing SCPI precursor gel with carbon fibers (CF) using vacuum impregnation method. The CFs can be recycled several times in high quality. This synthesis scheme of crosslinked PI provides a new idea for the sustainable development of thermoset PI.